Assessment of Environmental Protection Awareness among Universal Basic Education Students in Nigeria - Alimi, Olatunji Sabitu; Olatumile, Adekunle (Advances in Social Sciences Research Journal, 2016)
The 21st century is challenged by the problem of environmental degradation and hence is preoccupied by efforts geared towards the protection of the environment. A major target group is young children in schools. The universal basic education policy in Nigeria seems not to mainstream environmental literacy in the curriculum, therefore this study aims at assessing the level of environmental protection awareness of young children in Nigeria. The study employed the use of descriptive survey method. One hundred students were selected through stratified random sampling technique to cater for variables of religion, gender, school grade, accommodation and medium of communication. The sampled students responded to a twenty-two item questionnaire. Four hypotheses were formulated for the study. The SPSS computer software chi-square was used to test the hypotheses. Result of the study showed no significant difference between religion, gender, accommodation, medium of communication and environmental protection awareness. The study suggested that: environmental education should be infused into every subject; gender should be mainstreamed into environmental education curriculum; environmental education should be delivered in and out of school; formal and informal communication should be employed in environmental education; and environmental issue should equally be emphasized at both primary and secondary school levels.